2021
DOI: 10.1038/s41598-021-87159-1
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-induced inhibition of endoplasmic reticulum stress normalizes splenic CD4 + T lymphocytes following hemorrhagic shock

Abstract: The aim is to investigate that 17β-estradiol (E2)/estrogen receptors (ERs) activation normalizes splenic CD4 + T lymphocytes proliferation and cytokine production through inhibition of endoplasmic reticulum stress (ERS) following hemorrhage. The results showed that hemorrhagic shock (hemorrhage through femoral artery, 38–42 mmHg for 90 min followed by resuscitation of 30 min and subsequent observation period of 180 min) decreased the CD4+ T lymphocytes proliferation and cytokine production after isolation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Recent studies showed that ethinyl estradiol sulfate, an estrogenic derivative, blunted hemorrhagic shock induced-multiple harmful outcomes in rat and swine, and showed a broad prospect of clinical application (30,31). Our previous studies have demonstrated that E2 prolonged the survival time and normalized CD4 + T lymphocyte function of rats after hemorrhagic shock (19) and attenuated hemorrhagic shock-induced vascular hyporeactivity in mice (25). In this study, we applied the small animal pulmonary function assay system and confirmed that E2 treatment improved the pulmonary function evidenced by these indices including RI, FRC, PEF, and IC of hemorrhagic shock rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies showed that ethinyl estradiol sulfate, an estrogenic derivative, blunted hemorrhagic shock induced-multiple harmful outcomes in rat and swine, and showed a broad prospect of clinical application (30,31). Our previous studies have demonstrated that E2 prolonged the survival time and normalized CD4 + T lymphocyte function of rats after hemorrhagic shock (19) and attenuated hemorrhagic shock-induced vascular hyporeactivity in mice (25). In this study, we applied the small animal pulmonary function assay system and confirmed that E2 treatment improved the pulmonary function evidenced by these indices including RI, FRC, PEF, and IC of hemorrhagic shock rats.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm the intestinal lymphatic mechanism of E2 therapy on hemorrhagic shock–induced ALI, partial rats with acute hemorrhage received subcutaneous injection of E2 (2 mg/kg) upon resuscitation. The dose of E2 is referenced the previous report (19). The obtained PHSML and E2-PHSML (from E2-treated rats) were centrifuged at 3000 r/min for 10 min for cellular component removal and supernatant collection, which was frozen at −80°C for the next observation.…”
Section: Methodsmentioning
confidence: 99%
“…The expression levels of autophagic and phenotypic proteins were detected using western blotting. Primary antibodies, including LC3 II (1:1000, ab192890; Abcam, Cambridge, UK), Beclin 1 (1:1000, ab207612, Abcam), MMP2 (1:1000, 10,373-2-AP; Proteintech, Chicago, IL), Calponin 1 (1:5000, ab46794, Abcam), and β-actin (1:5000, 66009-1-IG, Proteintech), were used as previously described (26,27). Protein bands were visualized using an ultrasensitive luminescent solution sourced from Beijing Puli Gene Technology Co. (Beijing, China).…”
Section: Methodsmentioning
confidence: 99%
“…HS model was established as described previously (14). Rats were weighed and anesthetized using 3% iso urane (Hebei Yilin Pharmaceutical Co., LTD., Shijiazhuang, China) by inhalation, and then maintenance of anesthesia with an intraperitoneal injection of 1% pentobarbital sodium (50 mg/kg, Merck, Germany).…”
Section: Hs Model In Ratsmentioning
confidence: 99%